2015
DOI: 10.1371/journal.pone.0126017
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Perivascular Sympathetic and Nitrergic Innervation Function Induced by Late Pregnancy in Rat Mesenteric Arteries

Abstract: Background and PurposeWe investigated whether pregnancy was associated with changed function in components of perivascular mesenteric innervation and the mechanism/s involved.Experimental ApproachWe used superior mesenteric arteries from female Sprague-Dawley rats divided into two groups: control rats (in oestrous phase) and pregnant rats (20 days of pregnancy). Modifications in the vasoconstrictor response to electrical field stimulation (EFS) were analysed in the presence/absence of phentolamine (alpha-adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, a direct relationship between both neurotransmitters does not always appear, since we have also observed increased ATP together with decreased NO release 62 . Additionally, we have previously reported that modifications in NO release are independent of alterations in NA vasoconstriction 37 63 64 72 . Once again, these results seem to confirm that the possible interaction between the different components of perivascular innervation depends on the pathophysiological situation under study, and highlight the need for studying innervation function in different PH and cirrhosis models.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a direct relationship between both neurotransmitters does not always appear, since we have also observed increased ATP together with decreased NO release 62 . Additionally, we have previously reported that modifications in NO release are independent of alterations in NA vasoconstriction 37 63 64 72 . Once again, these results seem to confirm that the possible interaction between the different components of perivascular innervation depends on the pathophysiological situation under study, and highlight the need for studying innervation function in different PH and cirrhosis models.…”
Section: Discussionmentioning
confidence: 94%
“…Both results indicate a greater participation by the sympathetic co-transmitter ATP in LC rats. Purinergic contribution has been reported to depend on previous vascular tone, and is higher when tone is increased 37 57 59 62 63 64 . Taking this into account, the increased vasoconstrictor response to EFS in LC rats could be responsible for the enhanced ATP release observed in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to observed with endothelial NO [16,36], here we have shown that the supplementation of MtS rats with synbiotics restore neuronal NO release, reaching levels comparable in the CT group. NO released from nitrergic nerve terminals is able to decrease in a great extent the maximal arterial tone elicited by the sympathetic neurotransmitter noradrenaline [23,50]. In situations where the vascular resistance is increased, we have previously observed either a potentiation in nitrergic function, which aims to compensate the greater vascular resistance [23,51], or a blunted nitrergic role, thereby participating in the enhancement of peripheral vascular resistance a consequently, in the development of hypertension [47,49].…”
Section: Discussionmentioning
confidence: 97%
“…We tested this prediction by using submaximal electrical field stimulation (EFS) (40 V at 15 Hz) of MAs to release endogenous norepinephrine and ATP from sympathetic nerve terminals embedded in the vessel wall, thereby activating G q/11 -coupled ␣ 1 -adrenergic and P2Y2 purinergic GPCRs in vascular smooth muscle cells and triggering vasoconstriction (51)(52)(53). If the proteolytic half-life of RGS2 in MAs is similar to that of transfected RGS2 (ϳ30 min), then treating wild-type MAs 1 h with CHX would be sufficient for most of the preexisting pool of RGS2 to be degraded.…”
Section: Rgs2 Proteolysis Dynamically Regulates G Q/11 Signalingmentioning
confidence: 99%